Pengaruh Sustainability Reporting dan Profitabilitas terhadap Nilai Perusahaan Sektor Perbankan yang Terdaftar di Bei Tahun 2020-2024 - Nurul’aeni, Nia; Lasmini, Lilis; Purwandari, Dian (BUDGETING : Journal of Business, Management and Accounting, 2026)
ABSTRACT This study aims to analyze the impact of sustainability reporting and profitability on firm value among banking companies listed on the Indonesia Stock Exchange for the period 2020–2024. The study is based on Stakeholder Theory, which explains that companies are accountable to all stakeholders. Sustainability reporting is measured using the Sustainability Report Disclosure Index (SRDI) based on Global Reporting Initiative (GRI) standards; profitability is measured by Return on Assets (ROA); and firm value is measured using Price-to-Book Value (PBV). This study employs a quantitative approach using descriptive and confirmatory methods. The sample was selected using purposive sampling from banking companies that met the research criteria. The data used were secondary data obtained from the companies’ annual reports and sustainability reports. Data analysis was conducted using SmartPLS with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through outer model and inner model testing, as well as bootstrapping techniques. The results indicate that sustainability reporting has a non-significant negative effect on firm value, while the profitability variable has a non-significant negative effect on firm value in the banking sector. Keywords:  Firm Value, Profitability, Sustainability Reporting.